(3NUe GdChQGb GdJLGQjI (B/ s - (3CSGeI QCaJ EHQGgje GdLfOis; (3SGei YHOGdHGbi eMeO CHh UGdM s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3gi Jdc GdYedjI GdeUQajI GdJi jbhe ef NdGdgG GdHfc HGdOaY GdahQi dbjeI GdUc bHd ejYGO GdGSJMbGb Ch EjOGY gPg GdbjeI HMSGH GdYejd dOjg ebGHd fbd edcjJg Edi GdHfc(B: (3KbI efg ai GSJQOGO eG OaYg ai JGQjN GdGSJMbGb ef GdeOjf HGdUc(B: (3Ydi Cf jNUe GdHfc fSHI ef bjeI GdUc JSei SYQ GdNUe (B((3GdELjh(B) (3h GdJi JeKd YGFO GdeHdZ GdeOahY Yf GdeOI ef JGQjN OaYg Edi JGQjN GSJMbGb GdhQbI eY GdJRGe GdYejd HEYGOI GdbjeI GdESejI ddhQbI YfO YOe haGA GdeOjf GdCUdi(B: (3h dPG jUHM GdHfc MGedG ddUc eGfMG GFJeGfg djS dYejdg GdOGaY aMSH Hd ddeSMhH Ydjg GdbGFe HGdSOGO ai JGQjN GdGSJMbGbs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2018s
(3HHdjhLQGajG(B: (3UaMGJ (B533-593s
(3GdfU HGdYQHjI hGdedNU HGddZI GdaQfSjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdGYJeGO HGdNUes; (3GdfXGe GdbGfhfj dYedjI GdNUes; (3GdChQGb GdJLGQjIs; (3GdceHjGdIs; (3GdUchcs; (3GdTjcs; (3GdSfO GdEPfjs; (3GdChQGb GdJLGQjI GdEdcJQhfjIs; (3MGaXI Ojdjs; (3VeGfGJ YedjI GdNUes; (3GdbjO GdYcSjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs